2020
DOI: 10.1016/j.scitotenv.2020.139541
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 lockdown on PM10, SO2 and NO2 concentrations in Salé City (Morocco)

Abstract: • PM 10 , NO 2 and SO 2 concentrations were reduced by more than half during the covid-19 lockdown period. • Covid-19 countermeasures contribute to reduce all pollutant concentrations but with significant differences among them. • Long-range transported aerosols contributions overcame the PM 10 local emission reductions benefits related to the lockdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
202
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(235 citation statements)
references
References 14 publications
24
202
0
9
Order By: Relevance
“…Their results reveal that levels of polluting gases fell by about 45% after two weeks. Similar findings are reported in Thailand ( Stratoulias and Nuthammachot, 2020 ), China and Japan ( Ma and Kang, 2020 ; Zhang et al, 2020 ), Ecuador ( Zalakeviciute et al, 2020 ), Iran ( Broomandi et al, 2020 ), Milan, Italy ( Collivignarelli et al, 2020 ) and Morocco ( Otmani et al, 2020 ). Siciliano et al (2020) and Zhao et al (2020) , in turn, identified noteworthy increases in ozone concentrations (O 3 ) during the measures of social distancing adopted respectively by Brazil and China.…”
Section: Resultssupporting
confidence: 82%
“…Their results reveal that levels of polluting gases fell by about 45% after two weeks. Similar findings are reported in Thailand ( Stratoulias and Nuthammachot, 2020 ), China and Japan ( Ma and Kang, 2020 ; Zhang et al, 2020 ), Ecuador ( Zalakeviciute et al, 2020 ), Iran ( Broomandi et al, 2020 ), Milan, Italy ( Collivignarelli et al, 2020 ) and Morocco ( Otmani et al, 2020 ). Siciliano et al (2020) and Zhao et al (2020) , in turn, identified noteworthy increases in ozone concentrations (O 3 ) during the measures of social distancing adopted respectively by Brazil and China.…”
Section: Resultssupporting
confidence: 82%
“…Even in Wuhan City, China 30% reduction of NO 2 was also found in 2020 than 2019 (He et al 2020b). in Salé City, Morocco, the concentration of PM10, NO 2 and SO 2 were decreased respectively, by 75%, 96% and 49% within few days after implementation of COVID-19 lockdown (Otmani et al 2020).…”
Section: Discussionmentioning
confidence: 90%
“…In India, AOD reductions of up to 50% were perceived in New Delhi [5]. Otmani et al [53] found reductions of 75%, 49% and 96% for PM 10 , SO 2 and NO 2 in Salé City (Morocco). Also, emissions of NO 2 have been reduced up to 40% in Iraq compared to the pre-lockdown [54].…”
Section: Correlation Sars-cov-2 Infections With Meteorological and Aimentioning
confidence: 99%